Rak TOGA Dengan Penyimpanan Otomatis Berbasis Timer: Inovasi Teknologo Teptat Guna Untuk Meningkatkan Pendapatan kas Desa - Firnanda, Rizal Chandra; Novita Sari, Venti Dwi; Sukamdani, Dendi; Nazarina, Sefira Dewi; Sri Diyanti, Daffa Dwi (Yayasan Cendekia Gagayunan Indonesia, 2025)
The development of TOGA racks with timer-based automatic watering systems is an innovative solution to increase the productivity of medicinal plants in rural villages. This appropriate technology is designed to address the problems of irregular watering and labor constraints. Through qualitative descriptive methods and a community service approach, this study demonstrates that the automated system can reduce maintenance time by up to 70% while improving plant quality. The implementation of this program not only impacts increased TOGA harvest yields but also creates new income sources for the village treasury through the sale of processed products. With low production costs and operational ease, this technology has the potential to be developed as a village-based creative economy model.